Simple Radiated Noise Estimation Based on Datasets of SiC and Si IPMs for Inverter Use - Tadakuma, Toshiya; Rogers, Michael; Joko, Motonobu (Conference proceedings - IEEE Applied Power Electronics Conference and Exposition, 2023)
For the sake of rapid prototyping and product development, it is desirable to comprehend radiated noise characteristics of SiC and Si devices at the earliest steps of designing new inverter systems because end products are subject to electromagnetic noise regulations. However, there is no international standard for evaluating radiated noise directly, not only for single chips, but also 6in1 Intelligent Power Modules (IPMs). This paper introduces a method to estimate radiated noise current dependency based on the radiated noise datasets of SiC and Si IPMs obtained by applying an extended double pulse test. The estimation method is then compared to the results of an actual operating inverter for validation.